Safety and Efficacy of Lecoxen Cream on the Wound Healing and Scar of Cesarean Section: A Prospective Observational Clinical Trial - Andrea Tinelli; Sarah Gustapane; Martina Licchelli; Grazia Doria; Gaetano Panese; Camilla Schinzari; Davide Carati (IMR Press, 2024)
Background: One of the most popular surgical procedures is the cesarean section (CS), and one of the most prevalent side effects of this procedure is wound and scar issues. The aim of this prospective, short-term, placebo-controlled study was to evaluate the safety and effectiveness of a silicone-based medical device (Lecoxen cream, Ekuberg Pharma, Carpignano Salentino, Italy) in healing wounds and scars derived from cesarean sections in nulliparous women. Methods: Seventy-four nulliparous women, ranging in age from 18 to 45, and underwent CSs, were divided in two groups of treatment (Lecoxen cream or Vaseline). The quality of scar was examined using the Vancouver scar scale after 28 days, while wound healing was evaluated using the Redness, Edema, Ecchymosis, Discharge, and Approximation (REEDA) scale on the 14th day following CS. Results: The treatment with Lecoxen cream determined a statistically significant improvement (p < 0.001) of the wound healing state, in terms of redness, edema, ecchymoses and discharge. Even about Vancouver Scar Scale (VSS) score there was a significative improvement in the observed group in terms of vascularization, pigmentation, flexibility and height (p < 0.001). No adverse effects were reported from the use of Lecoxen cream in participants. Conclusions: Lecoxen cream proved to be a safe and efficient treatment for wounds from CSs, making it a valuable topical to accelerate the healing process and reduce the visibility of scars. Clinical Trial Registration: The study was registered with the ISRCTN registry (https://www.isrctn.com/), registration number: ISRCTN51125312.